An Electrochemical DNA Biosensor for Carcinogenicity of Anticancer Compounds Based on Competition between Methylene Blue and Oligonucleotides - Nor Diyana Md. Sani; Eda Yuhana Ariffin; Wong Sheryn; Mohd Asyraf Shamsuddin; Lee Yook Heng; Jalifah Latip; Siti Aishah Hasbullah; Nurul Izzaty Hassan (Sensors, 2019)
A toxicity electrochemical DNA biosensor has been constructed for the detection of carcinogens using 24 base guanine DNA rich single stranded DNA, and methylene blue (MB) as the electroactive indicator. This amine terminated ssDNA was immobilized onto silica nanospheres and deposited on gold nanoparticle modified carbon-paste screen printed electrodes (SPEs). The modified SPE was initially exposed to a carcinogen, followed by immersion in methylene blue for an optimized duration. The biosensor response was measured using differential pulse voltammetry. The performance of the biosensor was identified on several anti-cancer compounds. The toxicity DNA biosensor demonstrated a linear response range to the cadmium chloride from 0.0005 ppm to 0.01 ppm (R2 = 0.928) with a limit of detection at 0.0004 ppm. The biosensor also exhibited its versatility to screen the carcinogenicity of potential anti-cancer compounds.